Heterogeneous pro–poor targeting in India’s Mahatma Gandhi National Rural Employment Guarantee Scheme - Liu, Yanyan; Barrett, Christopher B. (International Food Policy Research Institute, 2012)
India’s Mahatma Gandhi National Rural Employment Guarantee Scheme (MGNREGS) is the largest public works employment project in the world. Its most direct poverty reduction pathway is through boosting employment and income for the poor. How effectively this direct transfer mechanism reduces poverty turns fundamentally on the degree to which MGNREGS targets its resources toward otherwise-poor households. To explore this question, we use the 2009/10 National Sample Survey data to describe patterns of seeking, rationing, and participation in MGNREGS. At the national level, we find that the self-targeting design of MGNREGS leads to greater rates of self-selection into the program by poorer and scheduled tribe or scheduled caste households. However, the administrative rationing of MGNREGS jobs is not pro-poor but, rather, exhibits a sort of middle-class bias. At the state level, roughly half of 27 states exhibit rationing and participation profiles that signal effective pro-poor targeting. The other half of India’s states struggle to avoid high rates and regressive patterns of administrative rationing of MGNREGS jobs to which the poor have a legal right. Our results suggest that MGNREGS can be effectively deployed to attract, employ and improve the well-being of poor rural households but there remains room for improvement and perhaps much to be learned from in-depth comparative analysis of MGNREGS program implementation across states.